(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Pakistan ranks fifth among high tuberculosis (TB) burden countries. Despite Directly Observed Treatment Short Course Strategy (DOTS) implementation, adherence is still poor and Pakistan stood fourth in multi-drug resistant (MDR-TB) cases. This study was conducted to assess tuberculosis treatment adherence among newly diagnosed pulmonary TB patients at TB clinic of tertiary care hospital, Lahore, and to study factors affecting it. Patients and methods: Between May 2021 and February 2022, cross-sectional study was conducted at outdoor based TB Clinic, Services Hospital, Lahore, interviewing 732 active pulmonary TB patients aged 18 to 65 receiving Anti Tuberculosis Treatment (ATT) for at least two months. Adherence was studied incorporating Morisky Medication Assessment Scale (MMAS) and World Health Organization multi-dimensional adherence model (WHO-MAM) in close-ended questionnaire, considering socio-demographic, patient, health system, and therapy-related factors. Those scoring < 6 on MMAS were categorized low adherents. SPSS Version 25 analysed data. Chi-square test and binary logistic regression explored adherence associations, with p<0.05 considered significant. Results: Out of 732 patients,350 (47.8%) males and 382 (52.2%) had mean age of 37.41±13.3 and 38.80±14.08 years respectively, with family income of 22062.86±19915.34 vs 23900.52±22153.02 rupees, knowledge score of 4.62±1.56 vs 4.68±1.55 and MMAS score was 6.57±1.21 vs 6.59±1.22, respectively. Low Adherence was in 64.2%.After adjusting, significant factors were age (AOR=12.378, 6.679-22.94), being unemployed (AOR=2.18, 0.253-0.815), low income (AR=2.678, 1.29-5.56), doctor’s availability (AOR=0.161, 0.067-0.383), non-co-operative staff (AR=6.902,3.197-14.889), distance travelled (AOR=12.056, 5.875-24.74), and adequate knowledge (AOR=3.583,1.699-7.557) Conclusion: Two-thirds (64.2%) of TB Clinic attendees had low adherence. Unemployment, older age, low income, and inadequate knowledge had higher odds of low adherence. Similarly non-cooperative staff and distance from facility significant affected adherence.